A Wireless Access Multimode Gateway System Applied in Internet of Vehicle - Mohsen Mohamed; Yunchuan Mao; Rui Zhang; Lianfeng Shen (Dianxin kexue)
A wireless access multimode gateway system was developed in order to solve the problems of the network share and external network access for wireless devices equipped in the cars to form the internet of vehicle（IoV）. By the gateway system, the wireless local area network（WLAN）can be established. The terminals within this WLAN can access the public mobile communication network such as 3G even 4G and external internet in the vehicles. First, the system architecture was given. Then, the design and development of the wireless access multimode gateway were described in detail including the hardware platform and application software. Meanwhile, the selection strategy of wireless access network was studied according to the different business classifications to obtain the corresponding weight distribution by using analytic hierarchy process, in order to achieve the optimum network performance. The test results show that the developed gateway accords with the design requests and has the reliable and stable performances.